2019
DOI: 10.1111/ruso.12275
|View full text |Cite
|
Sign up to set email alerts
|

The Third Shift? Gender and Empowerment in a Women’s Ecotourism Cooperative

Abstract: Ecotourism is lauded as a path toward sustainable development and women’s empowerment in rural areas around the world, but little is known about how gendered expectations shape its processes and outcomes. This paper employs an in‐depth qualitative case study of a female‐only ecotourism cooperative in rural Mexico to investigate how local gender dynamics influence women’s opportunities to benefit from ecotourism development. Findings show that women’s family and work commitments prevent their ability to devote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 55 publications
0
11
0
4
Order By: Relevance
“…A study has shown that maternal employment does not need to be consistently helpful for the children’s nutritional factors (Debela et al, 2021). Further, the literature has identified that women’s entrepreneurial aspirations are affected by the prevailing gender dynamics in society (Morgan & Winkler, 2020). However, it is also found that cash transfers without income-generating efforts save childcare time (Tonguet-Papucci et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that maternal employment does not need to be consistently helpful for the children’s nutritional factors (Debela et al, 2021). Further, the literature has identified that women’s entrepreneurial aspirations are affected by the prevailing gender dynamics in society (Morgan & Winkler, 2020). However, it is also found that cash transfers without income-generating efforts save childcare time (Tonguet-Papucci et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Apesar dos benefícios citados, também há a constatação de impactos negativos como a exploração das trabalhadoras e a problemática da divisão do trabalho. O que ocorre é que as mulheres acabam por acumular funções, pois seguem com a responsabilidade dos trabalhos domésticos e familiares, considerados invisíveis (Gentry, 2007;Díaz-Carrión, 2014;Morgan & Winkler, 2020;Fezeka & Stella, 2020).…”
Section: Inexistenteunclassified
“…Entre eles, está o sentimento de autoconfiança, bem-estar e empoderamento feminino. Entretanto, também é observado, nos artigos, que ainda existem barreiras culturais, sociais e econômicas a serem vencidas pelas mulheres nesse segmento (Doran, Schofield, & Low, 2018;Morgan & Winkler, 2020). Nesse sentido, encontram-se também sugestões para que se façam mais estudos sobre a participação das mulheres no segmento de aventura, a fim de que se possa compreender melhor a dinâmica dessa participação, bem como, consiga-se identificar o papel de redes que fornecem apoio à construção de experiências não normativas para mulheres no turismo de aventura.…”
Section: Inexistenteunclassified
“…2015; Guo y Jordan, 2021), incrementar la carga laboral de la mujer y consolidar una división sexual del trabajo que la precariza (e.g Schellhorn, 2010;Phommavong y Sörensson, 2014;Sánchez y Winkler, 2020),. o empobrecer a los sectores productivos tradicionales al apropiarse de recursos (naturales, humanos, económicos,…) necesarios para su funcionamiento…”
unclassified